النّصّ السّيريّ لأعلام نفوسة سير نساء إباضيات - بن زايد, أحمد محمد (Sharwes Scientific Journal, 2024)
Recently, the issue of women, their freedom, and their contribution to public life has represented a basic demand for the Arab renaissance. But historical papers, in the past, hide many of women’s achievements and their presence in public life at various levels. The demands of modernity were something new at times and strange and new at other times. If we search in history books and news stories, we find a distinct presence of women in the fields of politics and literature, but they are a modest presence in biographies and notable figures in number and content.In the context of what was written about the progress of the notables in the Nafusa Mountains, especially from the Ibadis - considering the Ibadis